The Comorbid Relationship Between Migraine and Asthma: A Systematic Review and Meta-Analysis of Population-Based Studies - Wang, Long; Deng, Zi-Ru; Zu, Mei-Dan; Zhang, Juan; Wang, Yu (Frontiers in Medicine, 2021)
Objective: Recent studies have indicated a pathophysiologic link between migraine and asthma. This meta-analysis aimed to comprehensively estimate the risk ratio for migraine in asthma as well that of asthma in migraine based on available evidence. Method: We systematically searched the electronic databases including Pubmed, Web of Science, and SCOPUS for population-based studies that measured either the odds or risk of asthma in subjects with migraine as well as that of migraine in subjects with asthma. The titles and abstracts were screened by two independent reviewers to identify eligible studies and this was followed by full-text review of the included studies. Newcastle-Ottawa Scale (NOS) was used to assess the risk of bias of included literatures. A meta-analysis was conducted with Review Manager 5.3 Software to calculate the odds ratio (OR) for case-control and cross-sectional studies and either relative ratio (RR) or hazard ratio (HR) for cohort studies and the source of heterogeneity was assessed. Subgroup and sensitivity analysis were conducted and the I2-test were used to assess the source of heterogeneity. The funnel plot, galbraith plot and Egger’ test were used to evaluate publication bias. Results: Fifteen published studies covering a total of 1188780 individuals were identified. Pooled analysis indicated that migraine was associated with increased odds (OR=1.54; 95%CI: 1.34~1.77) and risk for asthma (HR=1.42 ; 95%CI: 1.26~1.60), and asthma associated with increased odds (OR=1.45 ,95%CI: 1.22~1.72) and risk for migraine (HR=1.47, 95%CI: 1.41~1.52). Conclusion: Migraine is a potential risk indicator for asthma, and vice versa, asthma is a potential risk indicator for migraine. However, future prospective cohort studies are warranted to provide more evidence concerning the detailed association between migraine and asthma.